Challenges to Food Access Among Lewiston’s African Immigrants - Jacobus, Michelle; Jalali, Reza (Maine Policy Review, 2011)
Michelle Vasquez Jacobus and Reza Jelali present a case study of challenges to food access among African immigrants in Lewiston, Maine
Keywords: Maine; food access; African immigrants; Somalis; Lewiston